2020
DOI: 10.3389/fpsyg.2020.01468
|View full text |Cite
|
Sign up to set email alerts
|

Dignity Therapy Helps Terminally Ill Patients Maintain a Sense of Peace: Early Results of a Randomized Controlled Trial

Abstract: Introduction: Dignity Therapy (DT) is a brief, individualized, narrative psychotherapy developed to reduce psychosocial and existential distress, and promote dignity, meaning, and hope in end of life patients. Previous studies have shown that DT was effective in reducing anxiety and depression, and improving dignity-related distress. However, less is known about its efficacy on spiritual well-being. The aim of this study is to contribute to the existing literature by investigating the effects of DT on specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 43 publications
1
53
0
2
Order By: Relevance
“…Moreover, DT has been largely studied in Anglo-Saxon cultures; therefore, it is likely that its application in sociocultural contexts with different values requires some adjustments [10][11][12][13][14][15][16]. Studies on DT in Italy are poor and focused on its application by trained psychotherapists [17,18]. Current evidence suggests the need to investigate how DT can comprehensively work in different cultural contexts and real-life settings, to discover the time and resource commitments required to deliver DT and to explore the experience of professionals delivering it [9,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DT has been largely studied in Anglo-Saxon cultures; therefore, it is likely that its application in sociocultural contexts with different values requires some adjustments [10][11][12][13][14][15][16]. Studies on DT in Italy are poor and focused on its application by trained psychotherapists [17,18]. Current evidence suggests the need to investigate how DT can comprehensively work in different cultural contexts and real-life settings, to discover the time and resource commitments required to deliver DT and to explore the experience of professionals delivering it [9,[19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…62 For dignity-related distress, both significant 63 and nonsignificant decreases were reported. 62,73…”
Section: Resultsmentioning
confidence: 97%
“…In our study, we also hypothesized that writing about stressful events would have positive effects on the sense of coherence and sense of peace. Previous studies showed that different narrative interventions with patients with severe health conditions were effective in maintaining or increasing the sense of peace [ 38 , 39 ]. The use of narrative interventions designed to promote meaning and hope or to highlight mastery and values can help patients with chronic diseases restore a sense of peace.…”
Section: Discussionmentioning
confidence: 99%